2015
DOI: 10.1002/ejoc.201403577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Simplified Halogenated Chondramide Derivatives with Strong Cytostatic Properties

Abstract: Removing the methyl groups and the stereogenic centers from the ω‐hydroxy acid of the chondramides results in a significant drop in the cytotoxicity of these interesting depsipeptides. This effect can be almost compensated for by introduction of a second chlorine atom on the β‐tyrosine moiety of the natural products. These simplified chondramides are much easier accessible than natural chondramides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Also included for reference are data for chondramide C, chondramide C1, and dichlorodesmethyl chondramide C, a synthetic analogue in which all the substituents on the polyketide unit are removed. In previous studies, we found this derivative to have comparable activity to chondramide C (at least towards HCT‐116 cells) 12…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…Also included for reference are data for chondramide C, chondramide C1, and dichlorodesmethyl chondramide C, a synthetic analogue in which all the substituents on the polyketide unit are removed. In previous studies, we found this derivative to have comparable activity to chondramide C (at least towards HCT‐116 cells) 12…”
Section: Resultsmentioning
confidence: 72%
“…With hydroxy esters 5 and 16a in hand, we next focussed on the synthesis of the chondramide derivatives (Scheme ). Esterification of the OH functionality with chlorinated β‐tyrosine derivative 17 12 using the Steglich protocol27 gave the desired esters (i.e., 18 ) in excellent yield. Cleavage of the N ‐Boc ( tert ‐butoxycarbonyl) group and coupling with chlorinated tryptophan dipeptide A gave access to tripeptide esters 19 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations